2019
DOI: 10.3389/fbioe.2019.00306
|View full text |Cite
|
Sign up to set email alerts
|

STS-NLSP: A Network-Based Label Space Partition Method for Predicting the Specificity of Membrane Transporter Substrates Using a Hybrid Feature of Structural and Semantic Similarity

Abstract: Membrane transport proteins play crucial roles in the pharmacokinetics of substrate drugs, the drug resistance in cancer and are vital to the process of drug discovery, development and anti-cancer therapeutics. However, experimental methods to profile a substrate drug against a panel of transporters to determine its specificity are labor intensive and time consuming. In this article, we aim to develop an in silico multi-label classification approach to predict whether a substrate can specifically recognize one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…The combination of different features could depict protein sequences in a more comprehensive manner (Wang et al, 2019b ). As illustrated in Table 1 , using the combined features yield the ACC of 93.95% and the MCC of 0.8346, which are both higher than other PSSM-based features.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of different features could depict protein sequences in a more comprehensive manner (Wang et al, 2019b ). As illustrated in Table 1 , using the combined features yield the ACC of 93.95% and the MCC of 0.8346, which are both higher than other PSSM-based features.…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicates that the features based on PSSM have better performance in the prediction of T4SE when compared with other types of features. The combination of different features could depict protein sequences in a more comprehensive manner (Wang et al, 2019b). As illustrated in Table 1, using the combined features yield the ACC of 93.95% and the MCC of 0.8346, which are both higher than other PSSM-based features.…”
Section: Comparison Of Different Features and Their Combinations On Tmentioning
confidence: 99%
“…For the ROC curve, 1-specificity was plotted on the horizontal axis, and sensitivity on the vertical axis. LOO, K-Fold cross-validation, and independent testing are the most widely used methods for predictor evaluation (Mrozek et al, 2015;Cao and Cheng, 2016;Chen et al, 2017Chen et al, , 2018aChen et al, , 2019bPan et al, 2017;He et al, 2018He et al, , 2019Jiang et al, 2018;Xiong et al, 2018;Yu et al, 2018;Zhang et al, 2018;Ding et al, 2019;Feng et al, 2019;Kong and Zhang, 2019;Li and Liu, 2019;Lv et al, 2019a;Manavalan et al, 2019;Shan et al, 2019;Wang et al, 2019a;Wei et al, 2019a,b;Xu et al, 2019;Yu and Dai, 2019). That is the general machine learning evaluation methods (training, validation and testing) are used for optimized model evaluation.…”
Section: Model Evaluation Metrics and Methodsmentioning
confidence: 99%
“…We considered the unrated items as negative ratings, i.e., not relevant for the users. For the ONTO algorithm, we also assessed how using the n most similar items affects the results, with n varying from 1, 5,10,15,20,25,30, and all of the items.…”
Section: Methodsmentioning
confidence: 99%
“…This work concluded that using semantic similarity improves the classification of the chemical compounds. More recently, [25] used the structural similarity and the ChEBI semantic similarity assembled into a hybrid for predicting compounds subtracts suitable for membrane transporters. Other studies used the semantic similarity of ChEBI entities for recognition and confirmation of chemical compounds found in research documents [26,27].…”
Section: Introductionmentioning
confidence: 99%